Ultrasound-assisted aqueous extraction, LC-MS/MS analysis and radiomodulating capability of autochthonous Italian sweet cherry fruits. Issue 3 (8th March 2018) - Piccolella, Simona; Crescente, Giuseppina; Nocera, Paola; Pacifico, Francesca; Manti, Lorenzo; Pacifico, Severina
Abstract : A ready-to-use functional food from cherry fruits exerts radiomodulating capabilities. Abstract : The current cancer treatment scenario lacks drugs acting as both radiosensitizer and radioprotector agents. In this context, the radiomodulatory properties exerted by an aqueous extract from the fruits of the Italian Prunus avium cv. Della Recca (PaDRw) were investigated. The extract, obtained through an environmentally-friendly ultrasound-assisted extraction, seemed to act as a radioprotector at lower tested doses (25 and 50 μg mL −1 ) and a radiosensitizer at 400 and 500 μg mL −1 dose levels towards the neuroblastoma SH-SY5Y cell line, irradiated with four graded X-ray doses (0, 0.5, 2, and 4 Gy). The fractionation of PaDRw by Amberlite XAD-4 non-ionic polymeric resin, coupled to LC-UV-MS/MS techniques, proved to be efficient also in the disclosure of lower constituents. About 63% of the whole PaDRw extract was constituted of hexitol, followed by fructose (∼22.8%) and glucose (∼10.7%). Chlorogenic acids and flavonoids, which accounted only for ∼2.2%, were hypothesized to be the main actors in PaDRw-induced radiomodulation.